Indogermanische Forschungen : Zeitschrift für Indogermanistik und historische Sprachwissenschaft / Journal of Indo-European Studies and Historical Linguistics (De Gruyter, 1892)
Indogermanische Forschungen publishes contributions mainly in the areas of historical-comparative linguistics, historical linguistics, typology and characteristics of the languages of the Indogermanic language family. Essays on non-Indogermanic languages are also featured, provided that they coincide with the main focus of the journal with respect to methods and language history.